Violence Research in Northeast and Southeast Asia: Main Themes and Directions - Hensengerth, Oliver (International Journal of Conflict and Violence (IJCV), 2011)
The study analyses research on violence in the Northeast and Southeast Asia with respect to four types: political, urban, domestic and youth violence, highlighting current research themes, tendencies and gaps in violence research on and in the region, and identifying needs for further research. Commonalities and differences between countries and subregions are examined, along with a treatment of the colonial experience that influenced political violence in postcolonial countries.